Abnormal Brain MRI Findings in Anti-N-Methyl-D-Aspartate Receptor Encephalitis and Correlation With Outcomes - Lei, Chunyan; Chang, Xiaolong; Li, Haijiang; Zhong, Lianmei (Frontiers in Neurology, 2022)
Purpose: The reported prevalence of abnormal findings by brain magnetic resonance imaging (MRI) varies from 11% to 83% among patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. Here we investigated the prevalence in a sample of Chinese patients and explored correlations of abnormal MRI findings with clinical outcomes. Methods: This retrospective study analyzed a consecutive series of 52 patients with anti-NMDAR encephalitis admitted to our hospital. Patients were assigned to “MRI-normal” or “MRI-abnormal” groups based on brain MRI after admission. The groups were compared in terms of clinicodemographic characteristics as well as scores on the Mini-Mental State Examination (MMSE) and modified Rankin Scale (mRS) at 3 and 12 months after admission. Results: Thirty-seven patients (71.15%) showed abnormalities on brain MRI, and these patients were more likely to be men and to show abnormalities on electroencephalography rate. Patients who showed normal or abnormal MRI findings did not differ significantly in clinical symptoms, rates of mortality or relapse, or mRS scores at 3 or 12 months. However, patients with abnormal MRI showed significantly lower MMSE scores than those with normal MRI at 3 and 12 months. Conclusions: We found a high prevalence of abnormal MRI findings in our sample of Chinese patients with anti-NMDAR encephalitis. We also found that abnormal findings were associated with cognitive decline, although not necessarily with mortality or functional outcomes in the short or long term.